The complete guide to godly play an imaginative method for presenting scripture stories to children. - Berryman, Jerome W.. (Denver Morehouse Education Resources, 2002)
The volumes of Godly Play invite children in preschool through 6th grade to enter into our sacred stories. Based on Montessori method, Godly Play uses a careful telling of scripture stories, engaging story figures and a variety of creative activities to encourage children to seek and find their own answers to their faith questions. This unique approach to religious education invites children to wonder about themselves, God and the world in a way that is playful and meaningful to them. Godly Play respects the innate spirituality of children and encourages them to use their curiosity and imagination to experience the mystery and joy of God.
Training video : presentations for spring : Synagogue; Upper room; the holy trinity stories dvd
KO
LO
Keywords: Schoolbooks - Didactic material; Contains audio-visual material; 268.911 -- Godsdienstontwikkelingspsychologie en catechese van het kind